2017
DOI: 10.3390/polym9120653
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Template Molecularly Imprinted Polymer Based on SBA-15 for Selective Separation and Determination of Panax notoginseng Saponins Simultaneously in Biological Samples

Abstract: Abstract:The feasible, reliable and selective multi-template molecularly imprinted polymers (MT-MIPs) based on SBA-15 (SBA-15@MT-MIPs) for the selective separation and determination of the trace level of ginsenoside Rb 1 (Rb 1 ), ginsenoside Rg 1 (Rg 1 ) and notoginsenoside R 1 (R 1 ) simultaneously from biological samples were developed. The polymers were constructed by SBA-15 as support, Rb 1 , Rg 1 , R 1 as multi-template, acrylamide (AM) as functional monomer and ethylene glycol dimethacrylate (EGDMA) as c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
1
5
0
1
Order By: Relevance
“…Selectivity factor is defined by comparison of the peak areas using the multifiber SPME device with a NIP fiber. The values were 3.89, 3.49, 2.51, 3.1, and 2.95 for diazinon, parathion‐methyl, pirimiphos‐methyl, quinalphos, and isocarbophos, respectively, similar to those reported in some literature by multi‐template MIP‐SPE method . The results indicated that the multi‐MIP‐fibers possessed good selectivity to template molecules and their structural analogs.…”
Section: Resultssupporting
confidence: 83%
“…Selectivity factor is defined by comparison of the peak areas using the multifiber SPME device with a NIP fiber. The values were 3.89, 3.49, 2.51, 3.1, and 2.95 for diazinon, parathion‐methyl, pirimiphos‐methyl, quinalphos, and isocarbophos, respectively, similar to those reported in some literature by multi‐template MIP‐SPE method . The results indicated that the multi‐MIP‐fibers possessed good selectivity to template molecules and their structural analogs.…”
Section: Resultssupporting
confidence: 83%
“…After the stacking stage, the washing stage is intended to eliminate unwanted debasements from the cartridge, but the dissolvable elution must be updated by its ability to undermine contact between analysts and polymers. SPME has shown itself to be a normal device for its more points of interest, for example, effortlessness of activity, dissolvable less nature, and the accessibility of business strands [151][152][153]. In other methods, the matrix solid-phase dispersion is set up with olaquindox as the format, methacrylic corrosive as a utilitarian monomer, and EGDMA as the crosslinking specialist.…”
Section: Mip-based Sensors Of Solid-phase Extraction In Food Analysismentioning
confidence: 99%
“…Sun and coworkers fabricated mt-MIPs by using SBA-15 as solid support, the components of ginsenoside Rb1 (Rb1), ginsenoside Rg1 (Rg1) and notoginsenoside R1 (R1) as templates, acrylamide as a functional monomer and EGDMA as cross-linker [180]. According to chemical structure and functional groups of templates, the ratio of Rb1 to Rg1 to R1 of 44:43:13 in ethanol porogen was selected for preparation of mt-MIPs.…”
Section: Multi-template Mipsmentioning
confidence: 99%